Assessment of knowledge, preventive behaviours and risk perception related to Covid-19 among medical students of Rawalpindi - Mohi Ud Din, Syed Fawad Mashhadi, Saira Maroof, Syeda Gohar Fatima, Habib ur Rehman, Sana Sarfraz (Journal of Rawalpindi Medical College, 2021)
Objectives: The study was conducted to determine the knowledge, preventive behaviours and perception of risk related to Covid-19 among the medical students who are the front line workers and are more susceptible to be infected. Methodology: This analytical cross sectional study was conducted in medical students of 1st, 2nd and 3rd year MBBS of various medical institutions of Rawalpindi. Study duration was 5 months (March 2020 to July 2020). The sample size was 425. Age ranging from 18 to 21 and 273 (64.2%) comprised of females. The inclusion criteria were those students who gave consent and filled out the questionnaire and the exclusion criteria was who didn’t concede. The data was analysed on SPSS. Confidence interval was set to be 95% with 5% margin of error. Results: Most of the students were aware of the basic Covid-19 related knowledge like common symptoms, incubation period, transmission and the basic preventive measures which was on average higher than the previous studies conducted on medical students and on health care workers. Students were also having high level of performance in preventive behaviours in perspective of Covid-19 but risk perception is of moderate level. Conclusion: Participants were found to have high levels of knowledge related to Covid-19 except use of N95 masks and use of anti-viral drugs for treatment. Among self-reported preventive behaviours section, lowest score is related to frequency of cleaning and disinfecting items that can be easily touched with hands (i.e. door handles and surfaces). Participants had moderate risk perception despite having high levels of knowledge and high performance in self-reported behaviours. Keywords: Covid-19, medical students, risk perception